Prognostic value of acute cor pulmonale in COVID-19-related pneumonia: A prospective study - Beyls, Christophe; Martin, Nicolas; Booz, Thomas; Viart, Christophe; Boisgard, Solenne; Daumin, Camille; Crombet, Maxime; Epailly, Julien; Huette, Pierre; Dupont, Hervé; Abou-Arab, Osama; Mahjoub, Yazine (Frontiers in Medicine, 2022)
Background It is known that acute cor pulmonale (ACP) worsens the prognosis of non-coronavirus disease 2019 (COVID-19) acute respiratory distress syndrome (NC-ARDS). The ACP risk score evaluates the risk of ACP occurrence in mechanically ventilated patients with NC-ARDS. There is less data on the risk factors and prognosis of ACP induced by COVID-19-related pneumonia. Objective The objective of this study was to evaluate the prognostic value of ACP, assessed by transthoracic echocardiography (TTE) and clinical factors associated with ACP in a cohort of patients with COVID-19-related pneumonia. Materials and methods Between February 2020 and June 2021, patients admitted to intensive care unit (ICU) at Amiens University Hospital for COVID-19-related pneumonia were assessed by TTE within 48 h of admission. ACP was defined as a right ventricle/left ventricle area ratio of >0.6 associated with septal dyskinesia. The primary outcome was mortality at 30 days. Results Among 146 patients included, 36% (n = 52/156) developed ACP of which 38% (n = 20/52) were non-intubated patients. The classical risk factors of ACP (found in NC-ARDS) such as PaCO2 >48 mmHg, driving pressure >18 mmHg, and PaO2/FiO2 < 150 mmHg were not associated with ACP (all P-values > 0.1). The primary outcome occurred in 32 (22%) patients. More patients died in the ACP group (n = 20/52 (38%) vs. n = 12/94 (13%), P = 0.001). ACP [hazards ratio (HR) = 3.35, 95%CI [1.56–7.18], P = 0.002] and age >65 years (HR = 2.92, 95%CI [1.50–5.66], P = 0.002) were independent risk factors of 30-day mortality. Conclusion ACP was a frequent complication in ICU patients admitted for COVID-19-related pneumonia. The 30-day-mortality was 38% in these patients. In COVID-19-related pneumonia, the classical risk factors of ACP did not seem relevant. These results need confirmation in further studies.